Intrinsic Motivation, Transformational Leadership, and Employee Performance Enhancement Evidence from BPODT Medan - Putri Indriati; Soulthan Saladin Batubara; M. Chaerul Rizky (Jurnal Fokus Manajemen, 2026)
This research aims to analyze the influence of Intrinsic Motivation and Transformational Leadership on Employee Performance at the Lake Toba Authority Executive Agency (BPODT). As an authority managing a Super Priority Tourism Destination, BPODT demands high professionalism and synergy in executing its coordinative and authoritative functions. The research methodology employed is a quantitative approach with multiple linear regression analysis. Data was collected through questionnaires distributed to 86 BPODT employees. Instrument testing was conducted through validity and reliability tests, while hypothesis testing utilized t-test (partial), F-test (simultaneous), and coefficient of determination tests.Research findings indicate that partially, Intrinsic Motivation has a positive and significant effect on employee performance with 27.05 and significance 0.000. Conversely, Transformational Leadership partially does not significantly influence employee performance with a significance value of 0.243. However, simultaneously, both variables significantly influence employee performance with a significance value of 0.000. The Adjusted R Square value of 0.981 demonstrates that Intrinsic Motivation and Transformational Leadership contribute 98.1% to the employee performance variable, while the remaining 1.9% is influenced by other factors outside the research model. In conclusion, although leadership does not independently drive performance, the synergy between employees' internal motivation and strategic leadership direction serves as the primary key to organizational success in achieving Lake Toba tourism development targets.